PENGARUH KINERJA KEUANGAN PERUSAHAAN TERHADAP HARGA SAHAM - Eka Pertiwi, Dinal; Anjellita, Anjellita (Universitas Muhammadiyah Bengkulu, 2025)
This study aims to analyze the effect of company financial performance proxied by Return On Assets (ROA) and Earning Per Share (EPS) on stock prices in food and beverage subsector manufacturing companies listed on the Indonesia Stock Exchange for the period 2019–2023. The research method used is a quantitative method with a causality approach, using secondary data obtained from company financial reports, with a purposive sampling technique and a sample size of 65 observations, and analyzed using multiple linear regression. The results of the study indicate that partially ROA and EPS have a significant effect on stock prices, and simultaneously ROA and EPS also have a significant effect on stock prices in food and beverage subsector manufacturing companies. The conclusion of this study shows that company financial performance reflected through the efficiency of asset use and the ability to generate earnings per share is an important factor that influences stock price movements, so it can be used as a consideration for investors in making investment decisions. Keywords: Stock Price; Return on Assets; Earnings Per Share; Financial Performance; Capital Market